2023
DOI: 10.1080/09537104.2023.2200838
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from senescent platelets, their transcriptomes and proteomes?

Abstract: Research into the natural aging process of platelets has garnered much research interest in recent years, and there have long been associations drawn between the proportion of newly formed platelets in the circulation and the risk of thrombosis. However, these observations have largely been demonstrated in patient groups in which there may be underlying systemic changes that effect platelet function. Recent advances in technology have allowed in-depth analysis of differently aged platelets isolated from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…During the storage of the PCs, adverse changes in platelets—PSLs—occur [ 38 ]. The reasons why platelets lose their ability to aggregate and undergo intensified activation during storage remain unclarified [ 5 , 14 ]. Platelets, plasma and leukocytes present in the PC contain and release, inter alia, extracellular matrix metalloproteinases that affect the activity of platelets [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the storage of the PCs, adverse changes in platelets—PSLs—occur [ 38 ]. The reasons why platelets lose their ability to aggregate and undergo intensified activation during storage remain unclarified [ 5 , 14 ]. Platelets, plasma and leukocytes present in the PC contain and release, inter alia, extracellular matrix metalloproteinases that affect the activity of platelets [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that factors leading to platelet activation and damage include contact with a charged surface, changes in temperature and oxygen availability, and the presence of leukocytes and erythrocytes, cellular debris and enzymes. Researchers have studied the contents of RANTES, TGF-β, INF-γ, IL-1, IL-6, and IL-8 in PCs; the extracellular accumulation of histamine, PAI-1,VEGF and IL-6; and platelet lipid profile changes [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Changes in pH and changes in the concentration of lactate dehydrogenase, which is used as a marker of cell damage in cell cultures, were analyzed as potential causes of increased platelet activation [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%